PEMANFAATAN UBI JALAR UNGU (Ipomoea batatas var. Ayamurasaki) DALAM PEMBUATAN ES KRIM SINBIOTIK (UPN VETERAN JAWA TIMUR, 2015)
ABSTRACT Sinbiotik is a combination between probiotics and prebiotik. Sinbiotik ice cream is food products containing prebiotik are made by means of a standard ice cream mix ferment with probiotic bacterial culture with the addition of a purple sweet potato as a probiotic. The problems faced in the manufacture of ice-cream sinbiotik purple sweet potato is the absence of lactose on the filtrate of purple sweet potato so need the addition of skim milk that serves as the source for the growth of Lactobacillus casei lactose, improve the texture of ice cream and as protective materials (Cryoprotectant agent). The research method used is RAL which is composed of two factors, namely the factor I is the addition of skim milk (10; 15; 20% b/v) and factor II is the concentration of the starter (Lactobacillus casei) (2; 4; 6% v/v) with three replicates. The results showed that the best treatment is treatment of the addition of skim milk at 20% and the concentration of the starter (Lactobacillus casei) 4%. The treatment has a total value of lactic acid bacteria 8,909 log CFU/ml, the viability of lactic acid bacteria 94,153%, a total of 1,164% acid, degrees of melting 21,444 speed (min/5gr), 29, 667% overrun, 10,600% fat content, inulin 0,187% levels, and based on the assessment of organoleptik gives a sense of fondness level 156, scent 162,5 texture 133. Key words : ubi jalar ungu, sinbiotik, es krim